Globalization and Female Empowerment: Evidence from Myanmar - Teresa Molina; Mari Tanaka (Institute of Labor Economics (IZA), 2020)
This paper examines whether globalization promotes female empowerment by improving the jobs available to women. Previous work has documented that exporting causally improved working conditions at predominantly female garment factories in Myanmar. In this study, restricting to garment factory neighborhoods, we find that women living near exporting factories are significantly more likely to be working, have lower tolerance of domestic violence, and are less likely to be victims of domestic violence. Using distance to the international airport as an instrument for proximity to an exporting factory, we find similar results: higher employment rates, lower tolerance of domestic violence, and a decrease in the experience of physical violence.
Keywords: J12; F66; 330; female empowerment; domestic violence; globalization; trade; Myanmar